The current state of teaching Uzbek to foreign students in practice - Israilova , Zuhra Muxsin qizi (The Lingua Spectrum, 2026)
In recent years, Uzbekistan’s political, economic, and cultural influence on the international stage has steadily increased, and the expansion of cooperation with international organizations and foreign countries has significantly boosted interest in the Uzbek language. Today, Uzbek is taught in approximately 60 leading universities worldwide, as well as in over 100 educational and cultural centers, which strengthens its global position. (Web link, 2019). Moreover, the steady annual increase in the number of international students coming to Uzbekistan to pursue studies in various fields makes teaching Uzbek as a foreign language an urgent academic and methodological task. This article provides a comprehensive analysis of the current state of teaching Uzbek to foreign students. It examines the international spread of the language, intercultural integration, and the role of Uzbek in public diplomacy. The needs of students studying at various higher education institutions in Tashkent and the linguistic, methodological, and psychological challenges encountered during the learning process are also explored. To address these challenges, modern approaches are proposed, including the development of needs-based curricula, the use of integrative teaching methods, the creation of visual and multimodal materials, and the development of intercultural competence. The study’s findings contribute to improving the methodology of teaching Uzbek as a foreign language, creating an effective learning environment, and promoting the global development of the Uzbek language.